Global Alignment of Carbon Nanotubes via High Precision Microfluidic Dead‐End Filtration (Adv. Funct. Mater. 10/2022). (2nd March 2022) - Rust, Christian; Li, Han; Gordeev, Georgy; Spari, Manuel; Guttmann, Markus; Jin, Qihao; Reich, Stephanie; Flavel, Benjamin S.
Abstract : 1D Crystals The controllable alignment of carbon nanotubes (CNTs) in large‐area thin‐films has been a longstanding challenge to the scientific community. In article number 2107411, Benjamin S. Flavel and co‐workers develop a custom‐built micro‐fluidic filtration setup that can repeatedly produce globally aligned films over an area of 3.8 cm 2 from both positively and negatively charged CNTs.